Raising Public Awareness of the Hazards of Chemical Drug in Traditional Medicine - Yulianita P.I. Lestari; Nur Azmi Elfarisa; Nor Amelia; Nurul Rahmmi Wulandari (Comment: an International Journal of Community Development, 2021)
Traditional medicine with claims of naturalness, of course, cannot contain Medicinal Chemicals (BKO). However, until now the POM Agency still finds several traditional medicinal products in which BKO medicinal chemicals are mixed in traditional medicine which is the selling point for manufacturers. how to use it or even just to increase sales because consumers like traditional medicinal products that react quickly to the body. In unsafe products there can be biological or microbiological hazards consisting of parasites (protozoa and worms), viruses, and pathogenic bacteria that can grow and develop in foodstuffs, so that they can cause infection and poisoning in humans. Based on this, it is necessary to carry out activities to provide information to the public regarding checking the safety of a product. The purpose of this community service activity is to make the community more aware of the safety of both food and non-food products that are used in everyday life. Service activities are carried out by direct counseling methods offline. The counseling went very well and smoothly, as evidenced by the value of the post-test results which increased compared to the pre-test.